Hypovirulence of Colletotrichum gloesporioides associated with dsRNA mycovirus isolated from a mango orchard in Thailand - Suharto, Aditya R.; Jirakkakul, Jiraporn; Eusebio-Cope, Ana; Salaipeth, Lakha (MDPI, 2022)
The pathogenic fungus Colletotrichum gloeosporioides causes anthracnose disease, which is an important fungal disease affecting the production of numerous crops around the world. The presence of mycoviruses, however, may have an impact on the pathogenicity of the fungal host. Here, we describe a double-stranded RNA (dsRNA) mycovirus, which was isolated from a field strain of C. gloeosporioides, Ssa-44.1. The 2939 bp genome sequence comprises two open reading frames (ORFs) that encode for a putative protein and RNA-dependent RNA polymerase (RdRp). The Ssa-44.1 mycovirus is a member of the unclassified mycovirus family named Colletotrichum gloeosporioides RNA virus 1 strain Ssa-44.1 (CgRV1-Ssa-44.1), which has a phylogenetic similarity to Colletotrichum gleosporioides RNA virus 1 (CgRV1), which was isolated from citrus leaves in China. In C. gloeosporioides, CgRV1-Ssa-44.1 was shown to be linked to hypovirulence. CgRV1-Ssa-44.1 has a low spore transfer efficiency but can successfully spread horizontally to isogenic virus-free isolates. Furthermore, CgRV1-Ssa-44.1 had a strong biological control impact on C. gloeosporioides on mango plants. This study is the first to describe a hypovirulence-associated mycovirus infecting C. gloeosporioides, which has the potential to assist with anthracnose disease biological management.